Effects of exercise therapy on anxiety and depression in patients with COVID-19: a systematic review and meta-analysis - Tang, Ju; Chen, Liang-Liang; Zhang, Hongtao; Wei, Peifeng; Miao, Feng (Frontiers in Public Health, 2024)
With increasing rates of anxiety and depression during COVID-19, exercise treatment has drawn attention for its effects on COVID-19 patients with anxiety and depression.This study set out to assess the impact of exercise therapy on COVID-19 patients' anxiety and depression.: PubMed, EMBASE, Web of Science and Cochrane Library were used to search articles about exercise therapy as a means of treating anxiety and depression in COVID-19 patients from inception to April 30, 2023. The risk of bias was assessed by the Cochrane Collaboration bias risk tool. Data were pooled with the random effects model. RevMan version 5.4 was used for the statistical analyses. This work was registered in the PROSPERO database (registration number: CRD42023406439).Randomized clinical trials (RCTs) of COVID-19 patients with anxiety and depression were included to assess the impact of physical exercise on COVID-19 patients with anxiety and depression.6 studies including a total of 461 COVID-19 patients were analyzed in this meta-analysis. Overall, the meta-analysis showed that compared with the control group, exercise could significantly improve anxiety (SMD = -0.76; 95%CI : -0.96, -0.55; P < 0.00001), depression level (SMD = -0.39; 95%CI : -0.70, -0.09; P = 0.01), the PHQ-9 score (MD = -1.82; 95%CI : -2.93, -0.71; P = 0.001) and the sleep quality (SMD = -0.73; 95%CI :-1.32, -0.14; P = 0.01) in COVID-19 patients.The research provided evidence that exercise therapy is able to help COVID-19 patients experience less anxiety and depression and have better-quality sleep.